A concise Sri Lankan Malay dictionary = Kamus ringkas bahasa Melayu Sri Lanka : with meanings in standard Malay and English - Saldin, B. D. K.; Lim, Lisa.; Sri Lanka Malay Documentation Project ([Dehiwela] : Sri Lanka Malay Documentation Project, 2007)
Malay-English dictionary.
Includes bibliographical references (p. [57]).
Malay and English
Keywords: Malay language -- Sri Lanka -- Dictionaries -- English